A fungibilidade das tutelas de urgências e sua efetividade processual - Souto Júnior, Eliezer Queiroz de (2011)
In this dissertation, we sought to demonstrate that, despite the new procedural techniques exist, trying to become more effective by courts there, then, as a social need to give speed to the demands faced by the Brazilian judiciary. In this sense, it was observed that the principles become a potent weapon in the hands of judges and may give them a quicker exit procedure for cases that are presented to the Judiciary. And as a consecration of the principles are the values of justice, are a source of law and are applied by judges, can be perfectly used in the resolution of the dispute, upon the occurrence of gaps in the law. Was studied because, as it applies to fungibility between the urgency protections and what it can mean for the judiciary patriotism. Worked up an explanation of the urgency protections, making the need to see the exhibition of the debate the question of replacement of the injunction restraining and vice versa, considering that despite that, this last fact has not been well accepted by the doctrine. But it appeared that in accordance with Article 273, § 7 of the Code of Civil Procedure, it becomes possible to perform the exchange of a request for early relief done irregularly, for a precautionary measure, say, incidentally, the process of knowledge. And he came to the conclusion that denying the effect of commingling would somehow defy the current law stand, and the principle of diligence and reasonable duration of proceedings